2015
DOI: 10.12801/1947-5403.2015.07.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Harm Reduction or Psychedelic Support? Caring for Drug-Related Crises at Transformational Festivals

Abstract: Many of the EDM events known as "transformational festivals" provide psychedelic support spaces: volunteer projects caring for festivalgoers undergoing difficult drug experiences. Mostly drawn from the festival community, many volunteer carers ("sitters") subscribe to psychedelic culture discourse which frames these substances as aids to personal growth if handled appropriately. However, within the dominant paradigm of international drug prohibition, support projects must employ the contrasting discourse of ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…It is possible that the likelihood of therapeutic outcomes is dependent on the individual's affect and perceptions within the given context. Outcomes appear to be, at least partly, determined by a perceived sense of safety and/or support whilst entering psychedelic states (78,79). For some, greatest benefit may be achieved in the Amazon rainforest with a curandero, whilst for others a clinical setting may be more appropriate.…”
Section: Contextual Factorsmentioning
confidence: 99%
“…It is possible that the likelihood of therapeutic outcomes is dependent on the individual's affect and perceptions within the given context. Outcomes appear to be, at least partly, determined by a perceived sense of safety and/or support whilst entering psychedelic states (78,79). For some, greatest benefit may be achieved in the Amazon rainforest with a curandero, whilst for others a clinical setting may be more appropriate.…”
Section: Contextual Factorsmentioning
confidence: 99%
“…Recent years have also seen a further increase of awareness to issues of set and setting within the drug culture. This can be recognized in the growing prevalence of psychedelic harm reduction services in international events such as The Boom Festival and Burning Man (Carvalho et al, 2014, Ruane, 2015 as well as in the growing presence of printed and online ''psychedelic manuals'' which offer guidelines for creating favorable set and setting conditions (e.g. Fadiman, 2011;Kilham, 2014).…”
Section: Integrating Set and Setting Into Medicine And Culturementioning
confidence: 99%
“…Ethnographic research has confirmed the importance of services' cultural and policy contexts when assessing outcomes. For example, Portugal's decriminalisation of drug possession reduces fear of using checking services , whereas in Australia police use drug detection dogs to search festival crowds and arrest people for drug possession . In addition, drug prices are inflated in Australia, requiring a drug‐checking service user in Australia to give up a larger amount of money in order to donate a full dose of a drug for testing than in Europe (e.g.…”
Section: Introductionmentioning
confidence: 99%